The Right Tool for the Job: Detection of Soil-Transmitted Helminths in Areas Co-endemic for Other Helminths. - Maria V Periago; Renata C Diniz; Simone A Pinto; Anna Yakovleva; Rodrigo Correa-Oliveira; David J Diemert; Jeffrey M Bethony (Public Library of Science (PLoS), 2015)
Due to the recent increased use of the McMaster (MM) fecal egg counting method for assessing benzimidazole drug efficacy for treating soil-transmitted helminth (STH) infections, the aim of the current study was to determine the operational value of including the MM method alongside the Kato-Katz (KK) fecal thick smear to increase the diagnostic sensitivity when STHs are co-endemic with trematode helminths (e.g., Schistosoma mansoni).A cross-sectional study was conducted in school-aged children aged 4-18 years in the northeastern region of the State of Minas Gerais (Brazil), where Necator americanus, Ascaris lumbricoides, Trichuris trichiura, and S. mansoni are co-endemic. One fecal sample from each participant was collected and transported to the field laboratory for analysis. Coprological diagnosis was performed on each fecal sample by three different methods: Formalin-Ether Sedimentation (FES), KK and the MM technique. The diagnostic sensitivity and negative predictive value (NPV) of each technique was calculated using the combination of all three techniques as the composite standard. In order to determine the agreement between the three techniques Fleiss´ kappa was used. Both the Cure Rate (CR) and the Fecal Egg Count Reduction (FECR) were calculated using the two quantification techniques (i.e., the MM and KK).Fecal samples from 1260 children were analyzed. The KK had higher diagnostic sensitivity than the MM for the detection of both A. lumbricoides (KK 97.3%, MM 69.5%) and hookworm (KK 95.1%, MM 80.8%). The CR of a single dose of mebendazole varied significantly between the KK and MM for both A. lumbricoides (p = 0.016) and hookworm (p = 0.000), with lower rates obtained with the KK. On the other hand, the FECR was very similar between both techniques for both A. lumbricoides and hookworm.The MM did not add any diagnostic value over the KK in areas where both STHs and trematodes were co-endemic. The lower sensitivity of the MM would have an important impact on the administration of selective school-based treatment in this area since if only the MM were used, 36 (13.9%) children diagnosed with A. lumbricoides would have gone untreated.